Astroglial CB1 Cannabinoid Receptors Mediate CP 55,940-Induced Conditioned Place Aversion Through Cyclooxygenase-2 Signaling in Mice - Cong, Jin; Lu, Kangrong; Zou, Wenjie; Li, Ziming; Guo, Zhipeng; Tong, Xiangzhen; Zheng, Jiawei; Zhu, Jianping; Li, Shuji; Zhang, Wangming; Guo, Yanwu; Gao, Tian-Ming; et al. (Frontiers in Cellular Neuroscience, 2021)
Cannabinoids (CBs), such as phytocannabinoids, synthetic CBs, and endogenous CBs, can be neuroprotective, rewarding, or aversive. The aversive effects of CBs may hinder their medical and recreational applications. It is unknown which type of CB receptors mediates the direct aversive effects of synthetic CB CP 55,940 which is an analog of Δ9-tetrahydrocannabinol, the major psychoactive component of marijuana. In this study, we address this question by taking the advantage of systematic type 1 CB receptor (CB1R) knockout mice and conditional reinstatement of this receptor only in astrocytes. We show that CP 55,940 at a concentration of 1 mg/kg induces conditioned place aversion (CPA) and the CPA effect of CP 55,940 is mediated by the astroglial CB1Rs. Inhibiting cyclooxygenase-2 (COX-2) eliminates CP 55,940-induced CPA in mice that only express CB1Rs in astrocytes. These findings conclude that CPA effect of CP 55,940 is mediated by the astroglial CB1Rs through COX-2 signaling, suggesting that selective COX-2 inhibition or precise isolation of astroglial CB1R activity may be the strategy for treating aversive response of medical and recreational administrations of marijuana.